MANFAAT FINANSIAL PEMBINAAN DAN VERIFIKASI KOPI DALAM UPAYA PENINGKATAN MUTU KOPI : STUDI KASUS PROGRAM VERIFIKASI BINAAN PT NESTLÉ INDONESIA DI KABUPATEN TANGGAMUS - Tasya Juwita; Fembriarti Erry Prasmatiwi; Hurip Santoso (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
This study aims to determine the benefit of the empowerment and coffee verification through  verified and non-verified coffee farm financial analysis and sensitivity analysis due to the decline in production and selling prices, and also increase in production costs. From each type of farming, 36 farmers sample are drawn by simple random sampling method, which choose 23 farmers from Pulau Panggung Subdistrict (3 farmer group) and 13 farmers from Sumberejo Subdistrict (2 farmer group).  Data collection was conducted in January-March 2013. Benefits through the empowerment and verification is analyzed through financial feasibility analysis using criteria NPV, IRR, Net B/C, Gross B/C, and Payback Period.  Sensitivity analysis uses the possibility in decline in production by 68%, decrease in selling price by 25%, and rise in labor cost by 16.7%. The results showed that verified farms have the feasibility criteria of NPV, IRR, Net B/C, Gross B/C, and payback period (PP) each amounting to Rp32,200,565; 17.83%; 1.93; 1.45; and 7.18 years; whereas in the non-verified farm feasibility criteria each amounting to Rp6,796,334; 12.10%; 1.19; 1.09; and 9.49 years.  Sensitivity analysis using the cash cost showed that only production decline that led both types of farming being unfeasible unless the criteria based on PP. In analysis based on the total cost, the decline in production and selling prices led to both types of farming was also not feasible unless by the PP criteria. Keywords: Coffee quality, empowerment, financial feasibility, perception, verification